Agrarian policies and rural develop ment in Costa Rica: definition elements in the new international context - Mora Alfaro, Jorge (2005)
In the last two decades, the Costa Rican rural areas have been under considerable transformations. The changes occurred in the international context and the reorientation of the economic policies executed in the country, provoked the loom up of a more diverse productive structure and the enhancement of inequalities between the different agricultural producer groups. The extraordinary scientific and technological developments current in the contemporary society, the big differences in the knowledge generation or in access of it, the Southern nations economic aperture trends and the persistence of diverse producersʼ protection mechanisms in the Northern countries; as well as the stimulus to agricultural and agro-indus trial production for the international market, and the efforts to attract external investment, are some of the conditioning factors of large rural areas modifications. The difficulties of nume rous families to survive if dedicated exclusively to agricultural activities; the increase of the rural non-agricultural productive activities (tourism, services, agribusiness); the growth of rural non agricultural employment; and the expansion of the rural areasʼ multifunctionality, reduce the effectiveness of the prevailing perspectives, exclusively centered in agriculture, and the definition of sectorial policies and institutional initiatives without an articulator axis. A territorial perspective adoption and the agricultural and developmental policiesʼ redefinition, oriented to respond to the new conditions of rural areas, are necessary measures to stimulate the productive activitiesʼ growth, to encourage the advance of different country regions and to promote rural wellbeing. The rural social actorsʼ participation in these processes is a crucial factor to respond to the needs and particular demands of the diverse territories, and to promote local development in the rural spaces.